Wearing protective equipment (masks) during a pandemic – an administrative obligation to protect public health - Kirilova, Simonna (Law Journal of New Bulgarian University, 2022)
The COVID-19 pandemic has changed the world dramatically. We will probably never see it again as it was before the appearance of the virus. We have all witnessed things that were very far away from us and have now become part of our daily lives. The virus has settled among us, and fear has settled in our hearts. We got used to hide in our homes or behind our masks, to avoid contacts, hugs. All happening around the virus started to excite me a lot from the first months of its appearance in Bulgaria together with the introduction of the state of emergency. I started asking myself different questions and looking for their answers. All topics around the coronavirus continue to be discussed until today – vaccines, restriction of fundamental rights, wearing personal protective equipment. With the research I did, I tried to answer some basic questions, referring to different regulations, as well as to give different points of view to practicing lawyers, opinions of the World Health Organization, as well as my own view.